2016
DOI: 10.1016/j.nanoen.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Annealing-free efficient vacuum-deposited planar perovskite solar cells with evaporated fullerenes as electron-selective layers

Abstract: Pe r o v sk it e so l a r c el l s, v a c u u m-d epo sit io n , el ec t r o n -s el ec t iv e l a y er , h o l e bl o c k in g l a y er , C 60 a n d C 70 (f u l l er en es )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 50 publications
3
108
0
Order By: Relevance
“…Thus, only a few research groups have reported high-efficiency devices prepared by this method. 29,31,60,81,82 …”
Section: Thermal Vapor Depositionmentioning
confidence: 99%
“…Thus, only a few research groups have reported high-efficiency devices prepared by this method. 29,31,60,81,82 …”
Section: Thermal Vapor Depositionmentioning
confidence: 99%
“…), solution deposition is a simple and low-cost way to fabricate high efficiency PSCs. [5][6][21][22][23][24][25][26][27][28][29][30][31] Several researches have been reported in obtaining high quality perovskite films based on growth engineering, solvent engineering and so on. In 2016, M. Dar and his coworkers studied the impact of chloride on the conversion of lead halide into CH3NH3PbI3.…”
Section: Introductionmentioning
confidence: 99%
“…40 nm between FTO and CH 3 NH 3 PbI 3 ( Figure 8). It should also be noted here that the cell configuration of FTO/C 60 /CH 3 NH 3 PbI 3 /HSL/Au allows establishment of a cascading energetics sequence (Figure 7b), [26][27][28][29]36 making it possible to derive the electrons and holes in the cell upon illumination.…”
Section: Resultsmentioning
confidence: 95%
“…24,25 In comparison with [60]PCBM, the pristine C 60 with no bulky substituents is expected to be packed more densely to facilitate the intermolecular charge transport. [26][27][28][29][30] * Electrochemical Society Fellow. z E-mail: umeyama@scl.kyoto-u.ac.jp; imahori@scl.kyoto-u.ac.jp Actually, it was reported that the planar PSC device with C 60 ESL outperforms the device with [60]PCBM ESL in the p-i-n architecture, ITO/PEDOT:PSS (HSL)/CH 3 NH 3 PbI 3 /fullerene/Ag.…”
mentioning
confidence: 99%